The rift - (:unkn) unknown (My University, 2004)
The WTO Conference in Cancun did not strengthen the confidence of African countries in the globalization process proposed by the United States and Europe. It ended in failure. Supported by the community of non-governmental organizations, it sought to defend its rights and challenge a system that is both unjust and inefficient. Tariffs on agricultural products and manual activities in developed countries are high, particularly in the areas of food and clothing, sectors in which developing countries have a certain comparative advantage. In addition, developed countries, especially the United States, subsidize their agriculture, even for exports. These are unfair manoeuvres. Cotton production is characteristic of the situation, with overproduction due to the domestic subsidies of developed countries in this sector. The 25,000 U.S. cotton farmers receive more subsidies than 500 million Africans in development aid. Africa is seeking unity to combat and stop this dumping.
Keywords: African Research